1975
DOI: 10.1007/bf00116367
|View full text |Cite
|
Sign up to set email alerts
|

The validity of various fracture mechanics methods at creep temperatures

Abstract: A B S T R A C T The application of stress intensity factors derived from linear elastic fracture mechanics (LEFM) to fracture at creep temperatures has been considered. From tensile creep rupture tests on single edge notched and notched centre hole specimens of solution treated A.I.S.I. type 316 stainless steel, it is shown that a LEFM approach is inapplicable to predicting creep crack growth rates, whilst the net section stress is found to correlate well with the crack growth rates. These observations have be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

1978
1978
1999
1999

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(9 citation statements)
references
References 6 publications
0
9
0
Order By: Relevance
“…Therefore, the specimen with larger grain size will need more time for crack initiation and growth. Therefore, the creep crack growth rates must be inversely proportional to grain size as expressed in equation (3). The test results shown in Fig.…”
Section: Effect Of Grain Size On Green Crack Growthmentioning
confidence: 99%
“…Therefore, the specimen with larger grain size will need more time for crack initiation and growth. Therefore, the creep crack growth rates must be inversely proportional to grain size as expressed in equation (3). The test results shown in Fig.…”
Section: Effect Of Grain Size On Green Crack Growthmentioning
confidence: 99%
“…(5) The increase in the steady state crack growth rate with increasing degree of biaxial tensile state of stress (see (1)) can be explained, at least phenomenologically, from the findings (2) to (4).…”
Section: Work Hardening Near the Crack Tipmentioning
confidence: 99%
“…Various studies have reported success with K [17], the net section stress [22] and C* [23], although the validity of the characterising parameter is dependent on the loading, on the material, its creep ductility and its sensitivity to the environment [24]. Riedel [25] defined ti as the relaxation (or characteristic) time for the transition from small-scale yielding to steady state conditions to occur.…”
Section: Use Of Fracture Mechanics Parametersmentioning
confidence: 99%